Pengaruh media komik digital terhadap keterampilan membaca siswa kelas III SDN 19 sitiung - Maldin Ahmad Burhani; Muhammad Sukron; Liska Amelia Yasman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by Indonesian language learning which is still not optimal. The learning process does not use interesting media. Therefore, many students' learning outcomes are below the minimum completeness criteria. For this reason, researchers conducted research using digital comic media. The aim of this research is to determine the influence of digital comic media on students' learning outcomes for Indonesian language content theme 2, namely loving plants and animals in class III at SDN 19 Sitiung. This type of research is experimental. The design of this research is one group pretest-posttest design. The population in this study were all class III students at SD Negeri 19 Sitiung, Dhamasraya Regency. The sample in this research was taken using a sampling technique or saturated sample. The data collection technique was taken by giving a pre-test and post-test. The sample in this study amounted to 27 students. The research was conducted at SD Negeri 19 Sitiung. The time for carrying out this research was in the second semester of the 2023/2024 academic year, adjusted to the thematic learning schedule for class III Indonesian language content at SDN 19 Sitiung. Based on the results of the paired samples t test, the significance was 0.000<0.05. It can be concluded that there is an influence of digital comic media on students' learning outcomes with Indonesian language content theme 2, love plants and animals in class III at SDN 19 Sitiung. Based on research, digital comic media can have a very good influence on students' Indonesian language learning outcomes. Digital comic media can be used by teachers to relate lesson material to students' real world, make students active, and can improve student learning outcomes. Keywords: Digital Comic Media, Reading Skills, learning outcomes, Class III Elementary School Students.